Characterization and Probiotic Potential of Levilactobacillus brevis DPL5: A Novel Strain Isolated from Human Breast Milk with Antimicrobial Properties Against Biofilm-Forming Staphylococcus aureus - Ivan Iliev; Galina Yahubyan; Elena Apostolova-Kuzova; Mariyana Gozmanova; Daniela Mollova; Iliya Iliev; Lena Ilieva; Mariana Marhova; Velizar Gochev; Vesselin Baev (Microorganisms)
Lactobacillus is a key genus of probiotics commonly utilized for the treatment of oral infections The primary aim of our research was to investigate the probiotic potential of the newly isolated Levilactobacillus brevis DPL5 strain from human breast milk, focusing on its ability to combat biofilm-forming pathogens such as Staphylococcus aureus. Employing in vitro approaches, we demonstrate L. brevis DPL5′s ability to endure at pH 3 with survival rates above 30%, and withstand the osmotic stress often found during industrial processes like fermentation and freeze drying, retaining over 90% viability. The lyophilized cell-free supernatant of L. brevis DPL5 had a significant antagonistic effect against biofilm-producing nasal strains of Staphylococcus aureus, and it completely eradicated biofilms at subinhibitory concentrations of 20 mg·mL−1. Higher concentrations of 69 mg·mL−1 were found to have a 99% bactericidal effect, based on the conducted probability analysis, indicating the production of bactericidal bioactive extracellular compounds capable of disrupting the biofilm formation of pathogens like S. aureus. Furthermore, genome-wide sequencing and analysis of L. brevis DPL5 with cutting-edge Nanopore technology has uncovered over 50 genes linked to probiotic activity, supporting its ability to adapt and thrive in the harsh gut environment. The genome also contains multiple biosynthetic gene clusters such as lanthipeptide class IV, Type III polyketide synthase (T3PKS), and ribosomally synthesized, and post-translationally modified peptides (RiPP-like compounds), all of which are associated with antibacterial properties. Our study paves the way for the further exploration of DPL5, setting the stage for innovative, nature-inspired solutions to combat stubborn bacterial infections.